SMD Simulation of the Transition between DNA Pair Bases Assisted by Molecules - Santiago Tolosa Arroyo; Jorge A. Sanson Martin; Antonio Hidalgo Garcia (Novel Aspects on Chemistry and Biochemistry Vol. 1, 2023)
By using steered molecular dynamic (SMD) simulations, the free energy profile of the adenine to guanine transition in the gas and aqueous phases was obtained. The mechanism assisted by water and formic acid molecules was described by three different ways. Adenine is first hydrolytically deaminated, then the previously created hypoxanthine is oxidized, and finally, xanthine is aminated to guanine. In the gas phase these processes indicate a slow and not spontaneous conversion \((Δ G_9=4.07 kcal · mol^-1, k=5.59 · 10^-40 s^-1)\), and a lifetime for guanine of \(τ=7.75 · 10^+22 s\). The presence of solvent makes the transition more difficult by increasing the reaction energy to \(26.90 kcal · mol^-1\) and decreasing the rate of the process to \(1.63 · 10^-55 s^-1\). However, it decreases the energy of the deamination process to \(-9.63 kcal · mol^-1\) and the lifetime of guanine base to \(τ=6.85 · 10^+17 s\) when the process takes place in aqueous solution. According to these results, guanine may contribute to genefic mutations based on the lifetimes observed. At the molecular dynamic level, transition states and intermediate structures were examined. This enables tracking the mechanism over time and computing its kinetic and thermodynamic properties.